Chemistry Students’ Views on the Importance of English for Learning - Fisilmi Kaffah Sujarwo; Syifa Qanita; Wahyunengsih (Kirana Publisher (KNPub), 2026)
This study investigated 44 undergraduate chemistry students' perceptions of English for Specific Purposes (ESP) within their academic curriculum. ESP is considered vital for equipping students to comprehend complex scientific literature, write detailed laboratory reports, and engage with all chemistry-related academic materials. The research utilized a quantitative methodology, employing a structured questionnaire. Descriptive statistics analyzed student responses to pinpoint their learning priorities. Findings strongly indicate that students place a high value on ESP, particularly emphasizing the importance of reading comprehension and scientific writing skills. These skills directly correlate with their ability to grasp intricate chemical concepts and produce high-quality documentation. However, the study also revealed significant challenges, including a limited scientific vocabulary, difficulties mastering academic writing conventions, and a noticeable lack of confidence in speaking English in professional contexts. These obstacles underscore a pressing need for the development and implementation of more contextualized ESP instruction that leverages authentic, real-world materials relevant to chemistry. In summary, the results stress the imperative of designing comprehensive ESP programs that seamlessly integrate focused language skill development with core scientific learning objectives.